Bottom of the pyramid : a memoir of persevering, dancing for myself, and starring in my own life - Sioux, Nia (Harper Horizon, 2025)
"When you've been told over and over that you belong at the bottom, how do you come out on top? Dance Moms star and triple threat Nia Sioux shows the way via her story of resilience, triumph, and defining success for herself"--